In Harm's way : the pornography civil rights hearings - MacKinnon, Catharine A.; Dworkin, Andrea (London: Harvard University Press, 1997)
"edited by Catharine A. MacKinnon and Andrea Dworkin DIGITAAL TE RAADPLEGEN IN DE LEESZAAL"